Hindu, Sufi, or Sikh - Ramey, S. author. aut Link
XV, 222 p. 2 illus.
Keywords: By analyzing concrete examples of the creation of a heritage in the context of migration, this multi-sited ethnography considers the implications of representations of religions and diaspora for Sindhi Hindus and other similar communities.